Palaeointensity and palaeomagnetic study of Cretaceous and Palaeocene rocks from Western Antarctica - Shcherbakova, V. V.; Bakhmutov, V. G.; Shcherbakov, V. P.; Zhidkov, G. V.; Shpyra, V. V. (Geophysical Journal International, 2012)
A combined palaeodirectional and palaeointensity study of a representative collection of plutonic rocks from the Antarctic Peninsula batholith from the western part of the Antarctic Peninsula, near the Ukrainian Antarctic base 'Academik Vernadsky' were carried out. Petrographically, the collection includes gabbros, diorites and quartz diorites, tonalities, granodiorites and granites. The ages of igneous complex emplacement vary from 50 to 117 Ma with most of the rocks belonging to the Cretaceous Normal Superchron. The characteristic remanent magnetizations were isolated by stepwise thermal demagnetization over the temperature interval 440-590°C and their intensities amount to 95 per cent of the NRM. The geographic positions of palaeopoles do not contradict the ‘key poles’ of the Antarctic Peninsula between 90 and 60 Ma. A significant part of the collection was subjected to Coe-modified Thellier palaeointensity experiments with the pTRM checks, which yielded seven reliable palaeointensity determinations for seven different locations. The obtained VDMs are relatively low for all sites, being on average about half of the present day VDM. The analysis of available palaeointensity data for the Cretaceous, Miocene and Middle Jurassic indicates the existence of strong correlations between the mean VDM and VDM scatter versus the rate of reversals. However, due to the shortage of data, the correlations are not significant at the 5 per cent significance level.